Polish Domestic Tourism in the Face of SARS‑CoV–2 Pandemic - Piechaczek, Aneta (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The paper focuses on the tourism market in the face of the SARS‑CoV–2 pandemic. Its aim is to verify whether Polish tourism in this period actually recorded such a significant drop in interest. The research is based on secondary data from the reports of Statistics Poland concerning the use of accommodation facilities in Poland by both Poles and foreign tourists. Accommodation services offered by accommodation facilities constitute one of the basic tourist services included in the tourist market. Verifying their situation in the holiday season 2020 is therefore one of the easiest ways to estimate the impact of the pandemic on the tourism market in Poland. The paper also includes a comparison of data on Polish tourists in 2020 in relation to previous years. The research was conducted with the use of ANOVA analysis of variance.